VINTAGE PEDAGOGICS AS A SYSTEM OF PEDAGOGICAL KNOWLEDGE ABOUT EDUCATIONAL REALITY (EDUCATION IN THE 21ST CENTURY, 2023)
The article describes a new system of pedagogical knowledge ¬ vintage pedagogics, which accumulates the tasks of systematization, containerization, application in the context of a new educational reality and reflection of previously created, but relevant for the use of ideas, forms, methods of pedagogical interaction. The factors of the expediency of its special status in the system of pedagogical knowledge are given, the place in the system of social and humanitarian knowledge as a transformational buffer between the history of pedagogics and pedagogical innovation, functionally acting as a subsystem of educational management, is described. Constants, variable and often-innovative pedagogical reality components are characterized.
Keywords: Keywords: Vintage pedagogics, system of pedagogical knowledge, pedagogical interaction, education, pedagogical process, innovation.